2022
DOI: 10.1093/plphys/kiac013
|View full text |Cite
|
Sign up to set email alerts
|

2′,3′-cAMP treatment mimics the stress molecular response inArabidopsis thaliana

Abstract: The role of the RNA degradation product 2’,3’-cyclic adenosine monophosphate (2’,3’-cAMP) is poorly understood. Recent studies have identified 2’,3’-cAMP in plant material and determined its role in stress signaling. The level of 2’,3’-cAMP increases upon wounding, in the dark, and under heat, and 2’,3’-cAMP binding to an RNA-binding protein, Rbp47b, promotes stress granule (SG) assembly. To gain further mechanistic insights into the function of 2’,3’-cAMP, we used a multi-omics approach by combining transcrip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 56 publications
(92 reference statements)
1
6
0
Order By: Relevance
“…We speculate that 2′,3′-cAMP and 2′,3′-cGMP may up-regulate the expression of genes required for EDS1 signaling. This model agrees with a recent study showing that 2′,3′-cAMP induces many stress-related Arabidopsis genes ( 41 ).…”
Section: Discussionsupporting
confidence: 93%
“…We speculate that 2′,3′-cAMP and 2′,3′-cGMP may up-regulate the expression of genes required for EDS1 signaling. This model agrees with a recent study showing that 2′,3′-cAMP induces many stress-related Arabidopsis genes ( 41 ).…”
Section: Discussionsupporting
confidence: 93%
“…Examples of RNP condensates are the evolutionarily conserved processing bodies (PBs), and stress granules (SGs) ( Solis-Miranda et al 2023 ). The numbers and sizes of PBs and SGs depend on conditions; furthermore, the size of SGs depends on small metabolic molecules ( Chodasiewicz et al 2022 ). Under heat stress (HS), PB size can increase ( Gutierrez-Beltran et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with 10 μ m Br‐adenosine did not rescue the short‐hypocotyl phenotype of the act2act7 (Figure S3; Table S10), asserting the specificity of the 3′,5′‐cAMP action. No rescue was also measured for the positional isomer of 3′,5′‐cAMP, 2′,3’‐cAMP known as a stress signaling molecule (Chodasiewicz et al., 2022; Kosmacz et al., 2018) (Figure 4a,b). Finally, we showed that Br‐3′,5′‐cAMP concentrations as low as 100 n m , corresponding to the reported 3′,5′‐cAMP concentrations (low to middle range n m ) in plant cells (Moutinho et al., 2001), rescued the short‐hypocotyl phenotype of the act2act7 mutant (Figure 3d; Figure S4, Table S11).…”
Section: Resultsmentioning
confidence: 98%